PENGELOLAAN KEUANGAN PADA USAHA MIKRO KECIL MENENGAH DI KECAMATAN BIRINGKANAYA (Studi Kasus pada UMKM Asyiqah Konveksi) - Apriyandi, Apriyandi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
Micro, Small and Medium Enterprises (MSMEs) Asyiqah Konveksi is the topic of this study on financial management in Micro, Small and Medium Enterprises (MSMEs). The purpose of this study is to determine the financial management of small, micro, and medium enterprises in MSME Asyiqah Konveksi. Asyiqah Konveksi is a type of business in the field of mass production of ready-to-wear clothing located in Kupang Permai Housing, Biringkanaya District, Makassar City, South Sulawesi. This business was founded in 2019. Behind the success of MSME Asyiqah Konveksi, there are still problems faced, especially in poor financial management. The research design on this MSME uses observation data collection and semi-structured interviews included in the qualitative methodology. Based on observations and interviews with MSME Asyiqah Konveksi, it can be said that the financial management carried out in this business is still not optimal in terms of financial management, financial management is only managed by the business owner (owner) himself. In addition, the recording carried out by the owner is still very simple with a manual system, namely recording which is still written in the cash book manually and the recording is not complete according to financial accounting rules.